Magnesium battery rare earth chloride electrolyte and preparation method and use method thereof

By forming a dense product layer in the magnesium air battery by rare earth chloride electrolyte, the problems of magnesium anode corrosion and insoluble product deposition are solved, and efficient and low-cost battery performance improvement is achieved.

CN120545570AActive Publication Date: 2025-08-26NORTHEASTERN UNIV CHINA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511036675.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-28
Publication Date
2025-08-26
Estimated Expiration
2045-07-28

AI Technical Summary

Technical Problem

During the discharge process of magnesium air battery, contact of magnesium anode with the electrolyte causes hydrogen and insoluble products to be deposited by side reactions, affecting the output voltage and power stability of the battery, and the utilization rate of anode material is low. The existing electrolyte preparation methods are complex and costly.

Method used

A rare earth chloride electrolyte is used, and the components include 0.45-0.65M sodium chloride, 0.4-0.6M yttrium chloride, and 0.4-0.6M gadolinium chloride. By adjusting the pH to 7±0.2, a dense discharge product layer is formed to inhibit the generation of insoluble products and improve the anode utilization efficiency.

Benefits of technology

The discharge voltage and anode utilization efficiency of magnesium air batteries are significantly improved. The magnesium anode has increased by about 822.3 mgh g-1, the discharge voltage has been increased to 1.61V, and the anode utilization efficiency has been increased to 82.2%, which is environmentally friendly and has low preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120545570A_ABST
    Figure CN120545570A_ABST
Patent Text Reader

Abstract

The invention provides a magnesium battery rare earth chloride electrolyte as well as a preparation method and a use method thereof, and belongs to the technical field of magnesium air battery electrolytes.The magnesium battery rare earth chloride electrolyte comprises the following components in mole fraction: 0.45-0.65 M of sodium chloride, 0.4-0.6 M of yttrium chloride and 0.4-0.6 M of gadolinium chloride; and the pH value of the electrolyte is 7 + / -0.2. According to the magnesium battery rare earth chloride electrolyte as well as the preparation method and the use method thereof, the problems that a current Mg-0. 2Ca anode material is easy to corrode due to high electrochemical activity, the utilization efficiency of an anode is low, insoluble Mg (OH) 2 is easy to generate and deposit on the surface of the anode in the discharge process, and the discharge voltage of the anode is reduced can be solved; and preparation and use are economical, efficient and environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium-air battery electrolytes, and in particular to a magnesium battery rare earth chloride electrolyte and a preparation method and a use method thereof. Background Art

[0002] The increasing depletion of fossil energy has become a serious global challenge. Among various types of air batteries, magnesium-air batteries (Mg-air batteries) have attracted widespread attention due to their unique advantages. The energy conversion process in Mg-air batteries essentially utilizes a pair of spontaneous redox reactions: the oxidation of magnesium and the reduction of oxygen. The chemical energy released in this reaction forces electrons to flow from the negative electrode (Mg) through an external circuit to the positive electrode (O2), generating usable current (electrical energy). Ion migration in the electrolyte ensures charge balance within the battery, enabling the reaction to proceed continuously. Ultimately, chemical energy (stored in Mg and O2) is efficiently converted into electrical energy (to drive an external load) and chemical energy (stored in the reaction product, Mg(OH)2).

[0003] Although lithium-air batteries have the ability to charge and discharge, because lithium is more chemically active than magnesium, they must be operated in a glove box. If placed directly in air, the lithium is prone to spontaneous combustion, especially at high temperatures. Lithium reacts more violently when exposed to water, posing not only a significant safety hazard but also high lithium resources and a relatively low theoretical specific capacity. While zinc-air batteries offer excellent safety and low cost advantages, they struggle to achieve high voltage output due to the relatively low activity of zinc metal. During the discharge process of aluminum-air batteries, a stable passivation film forms on the aluminum electrode surface, inhibiting the continued discharge reaction and causing the electrode potential to rise, leading to a gradual decrease in output voltage and power.

[0004] In contrast, magnesium-air batteries offer even more significant performance advantages. Magnesium metal has a high electronegativity and high chemical activity, resulting in high theoretical specific capacitance and voltage. Furthermore, it is easy to process and relatively safe to use, making it a hot topic of research in recent years.

[0005] Magnesium-air batteries have broad application prospects and can be used in submarine power systems, remote communication equipment, and field emergency power supply.

[0006] However, magnesium-air batteries face the following practical problems. During discharge, the magnesium anode's continuous contact with the electrolyte triggers a side reaction with hydrogen ions in the electrolyte, producing hydrogen gas and insoluble discharge products such as magnesium hydroxide (Mg(OH)2). These products deposit on the anode surface, hindering contact between the anode and the electrolyte and affecting the stability of the battery's output voltage and power. Furthermore, excessive cathode hydrogen evolution can exacerbate magnesium corrosion, causing some magnesium not involved in the discharge reaction to become encapsulated and fall off, reducing anode material utilization and specific capacity, and shortening the battery's lifespan.

[0007] In order to improve the discharge performance of magnesium-air batteries, there are currently two main technical paths: one is to optimize the anode material, and the other is to adjust the chemical composition of the electrolyte. In terms of optimizing the anode material, alloying or heat treatment processes are often used. For example, by introducing elements such as calcium, the negative impact of impurity elements (such as iron and manganese) on the magnesium matrix can be weakened, the potential difference between the second phase and the matrix can be reduced, and thus the corrosion resistance can be improved; heat treatment processes such as low-temperature tempering can improve the alloy structure, promote uniform dissolution of the anode, and improve discharge stability. However, such methods usually require expensive processing equipment and long processing cycles, are not cost-effective, and have limited improvement in discharge performance.

[0008] Adjusting the electrolyte composition is a more efficient, economical, and environmentally friendly strategy. By optimizing the chemical composition ratio of the electrolyte, side reactions can be effectively inhibited and the formation of insoluble products can be reduced, thereby significantly improving the discharge voltage, anode utilization efficiency, and overall battery performance. Therefore, optimizing the chemical composition and ratio of the electrolyte is of great significance for promoting the application of magnesium-air batteries. However, current research on electrolytes is still in its early stages, and the developed electrolytes still have many shortcomings.

[0009] For example, the patent application number CN202410882642.2 proposes a mixture of disodium hydrogen phosphate and sodium acetate as the electrolyte of magnesium-air batteries. It shows the discharge voltage under three current densities, indicating that the discharge voltage of the anode is the highest in 0.005M / L sodium acetate and 0.5M / L sodium acetate. However, the anode discharge voltage is not stable, and the initial discharge process shows a very obvious voltage drop, which cannot provide stable output power. At the same time, when the anode current density increases to 10mA cm -2 When the electrolyte is used as the electrolyte, the effect of increasing the output voltage of the magnesium anode is weak, and the average discharge voltage of the anode is lower than 1.3V, indicating that the electrolyte is not suitable for use under high current density.

[0010] Another example is the patent application number CN202211577325.7, which proposes an ionic liquid electrolyte synthesized from 0.1 mol of choline hydroxide, 0.1 mol of glycolic acid and 0.1 M salicylic acid to improve the performance of magnesium-air batteries. This method can increase the voltage of magnesium alloys because the salicylic acid part in the ionic liquid can achieve the effect of Mg 2+ However, the synthesis of ionic liquids requires stirring and reacting for 12-24 hours at room temperature. After the reaction, it needs to be subjected to complex treatments such as rotary evaporation and drying. The overall process is complex and the cost is high. On the other hand, ionic liquids will reduce the ion transfer rate and affect the discharge voltage. At 5mA cm -2 At this current density, the average discharge voltage of the anode in 0.1 M choline salicylate electrolyte is only 1.368 V.

[0011] Therefore, there is an urgent need for an economical, efficient and environmentally friendly electrolyte and its preparation method to effectively solve the problems of the current Mg-0.2Ca anode material having high electrochemical activity and easy corrosion, low anode utilization efficiency, and the easy generation of insoluble Mg(OH)2 deposition on the anode surface during electrolysis, which reduces its discharge voltage. Summary of the Invention

[0012] The technical problem to be solved by the present invention is to provide an economical, efficient and environmentally friendly magnesium battery rare earth chloride electrolyte and its preparation method and use method, so as to solve the problems of the current Mg-0.2Ca anode material having high electrochemical activity and easy corrosion, low anode utilization efficiency and easy generation of insoluble Mg(OH)2 deposition on the anode surface during discharge, thereby reducing its discharge voltage.

[0013] In order to solve the above technical problems, the present invention provides a rare earth chloride electrolyte for a magnesium battery, which comprises, by mole fraction, 0.45-0.65M sodium chloride, 0.4-0.6M yttrium chloride, and 0.4-0.6M gadolinium chloride; The pH of the electrolyte is 7±0.2.

[0014] The present invention also provides a method for preparing a rare earth chloride electrolyte for a magnesium battery, comprising the following steps: Taking required amounts of sodium chloride, yttrium chloride and gadolinium chloride and mixing them evenly to obtain a mixture; Add the mixture into deionized water and heat and stir until a transparent solution is obtained; Dilute hydrochloric acid or sodium hydroxide is added to the transparent solution to adjust the pH of the solution to 7.0±0.2 to obtain the electrolyte.

[0015] Furthermore, the stirring speed is controlled at 200-300 rpm / min.

[0016] Furthermore, the heating temperature is 50±5°C.

[0017] Furthermore, the pH of the transparent solution is detected using a pH-conductivity meter.

[0018] The present invention also provides a method for using a rare earth chloride electrolyte for a magnesium battery, comprising the following steps: Apply an external current to the electrochemical workstation; Collect battery voltage change signals; A magnesium anode and an air cathode are inserted into the electrolyte to perform electrolysis.

[0019] Furthermore, the current density applied by the electrochemical workstation is 2.5 to 10 mA cm -2 .

[0020] Furthermore, the magnesium anode is a Mg-0.2Ca anode, with a magnesium content of ≥99.9wt.%, a calcium content of ≥0.2wt.%, a tin content of 0.01-0.012wt.%, and a content of impurities such as manganese ≤0.01wt.%.

[0021] Furthermore, 10-15% of the surface area of ​​the magnesium anode is exposed on the surface of the electrolyte.

[0022] Furthermore, the air cathode is prepared by using materials including copper mesh, graphite powder, and foil through pressing and shearing at a pressure of 450 to 550 MPa.

[0023] The present invention provides a rare earth chloride electrolyte for magnesium batteries, which uses sodium chloride, yttrium chloride and gadolinium chloride as components of the electrolyte. sp Both are less than the K of Mg(OH)2 sp , that is, K sp Y(OH)3 / Gd(OH)3 <K sp Mg(OH)2, during the electrolysis process, yttrium chloride and gadolinium chloride can react with OH produced by electrolysis. - The reaction generates precipitation, forming a thin and dense discharge product layer on the surface of the magnesium anode, which can effectively avoid the formation of a loose and thick discharge product layer, enhance the discharge performance of the magnesium anode, and thus effectively improve the discharge voltage and anode utilization efficiency of the magnesium-air battery, meeting the application of magnesium-air batteries in small long-distance communication equipment and other aspects.

[0024] Furthermore, the rare earth chloride electrolyte for magnesium batteries provided by the present invention can significantly improve the utilization efficiency of the magnesium anode, increasing it to 82.2%. Furthermore, compared to NaCl electrolyte, the rare earth chloride electrolyte provided by the present invention can not only increase the specific capacitance of the magnesium anode by approximately 822.3 mgh g-1 It can also increase the discharge voltage of the magnesium anode from 1.59 to 1.61V. The discharge potential is stable and can be applied to various current densities.

[0025] Furthermore, the magnesium battery rare earth chloride electrolyte provided by the present invention is formulated using non-toxic, harmless, and relatively inexpensive sodium chloride, yttrium chloride, and gadolinium chloride. It is not only environmentally friendly, but also has a relatively low production cost and high economic benefits. Furthermore, its preparation method is simple, easy to prepare, and convenient and fast. It has great application potential and is worthy of promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A flow chart of a method for preparing a rare earth chloride electrolyte for a magnesium battery provided in an embodiment of the present invention; Figure 2 (a) is an impedance analysis graph of the Mg-0.2Ca anode immersed in the electrolyte prepared in Comparative Example 1 for 20 min, 1 h, 3 h, 6 h, 12 h, and 24 h, respectively; Figure 2 (b) shows the impedance analysis of the Mg-0.2Ca anode immersed in the electrolyte prepared in Example 1 for 20 min, 1 h, 3 h, 6 h, 12 h, and 24 h, respectively; Figure 2 (c) shows the impedance analysis of the Mg-0.2Ca anode immersed in the electrolyte prepared in Example 2 for 20 min, 1 h, 3 h, 6 h, 12 h, and 24 h, respectively; Figure 2 (d) shows the impedance analysis of the Mg-0.2Ca anode immersed in the electrolyte prepared in Example 3 for 20 min, 1 h, 3 h, 6 h, 12 h, and 24 h, respectively; Figure 3 Potentiodynamic polarization diagrams of the Mg-0.2Ca anode immersed in the electrolytes prepared in Comparative Example 1 and Examples 1-3 of the present invention for 3 h and 24 h, respectively; Figure 4 The macromorphologies of the Mg-0.2Ca anode immersed in the electrolytes prepared in Comparative Example 1 and Examples 1-3 of the present invention for 7 days, wherein (a) is a macromorphology of the Mg-0.2Ca anode immersed in the electrolyte prepared in Comparative Example 1 for 7 days, (b) is a macromorphology of the Mg-0.2Ca anode immersed in the electrolyte prepared in Example 1 of the present invention for 7 days, (c) is a macromorphology of the Mg-0.2Ca anode immersed in the electrolyte prepared in Example 2 of the present invention for 7 days, and (d) is a macromorphology of the Mg-0.2Ca anode immersed in the electrolyte prepared in Example 3 of the present invention for 7 days; Figure 5 Graph showing discharge potential of the Mg-0.2Ca anode discharged for 10 h at different current densities in the electrolytes prepared in Comparative Example 1 and Examples 1-3 of the present invention; Figure 6The Mg-0.2Ca anode was used in the electrolytes prepared in Comparative Example 1 and Examples 1-3 of the present invention at 10 mA cm -2 Surface morphology after discharge for 10 h at a current density of 10 mA cm -2 Surface morphology of the Mg-0.2Ca anode at 10 mA cm-1 after discharge at a current density of 50 μm and 5 μm respectively. (b) is the surface morphology of the Mg-0.2Ca anode at 10 mA cm-1 in the electrolyte prepared in Example 1 of the present invention. -2 Surface morphology of the Mg-0.2Ca anode at 10 mA cm-1 after discharge at a current density of 50 μm and 5 μm respectively. (c) is the surface morphology of the Mg-0.2Ca anode at 10 mA cm-1 in the electrolyte prepared in Example 2 of the present invention. -2 Surface morphology of the Mg-0.2Ca anode at 10 mA cm-1 after discharge at a current density of 50 μm and 5 μm respectively. (d) is the surface morphology of the Mg-0.2Ca anode at 10 mA cm-1 in the electrolyte prepared in Example 3 of the present invention. -2 Surface morphology images after 10 h of discharge at the same current density with microscope scale lengths of 50 µm and 5 µm respectively; Figure 7 The Mg-0.2Ca anode was used in the electrolytes prepared in Comparative Example 1 and Examples 1-3 of the present invention at 10 mA cm -2 Graph of hydrogen evolution at the anode during 10 h discharge at different current densities. DETAILED DESCRIPTION

[0027] An embodiment of the present invention provides a rare earth chloride electrolyte for a magnesium battery, which comprises, by mole fraction, 0.45-0.65M sodium chloride, 0.4-0.6M yttrium chloride, and 0.4-0.6M gadolinium chloride; The pH of the electrolyte is 7±0.2.

[0028] The rare earth chloride electrolyte for magnesium battery provided by the present invention uses sodium chloride, yttrium chloride and gadolinium chloride as the components of the electrolyte. sp Both are less than the K of Mg(OH)2 sp , that is, K sp Y(OH)3 / Gd(OH)3 <K sp Mg(OH)2, during the electrolysis process, yttrium chloride and gadolinium chloride can react with OH produced by electrolysis. - The reaction generates precipitation, forming a thin and dense discharge product layer on the surface of the magnesium anode, which can effectively avoid the formation of a loose and thick discharge product layer, enhance the discharge performance of the magnesium anode, and thus effectively improve the discharge voltage and anode utilization efficiency of the magnesium-air battery, meeting the application of magnesium-air batteries in small long-distance communication equipment and other aspects.

[0029] Compared with NaCl electrolyte, the rare earth chloride electrolyte provided by the present invention can increase the specific capacitance of magnesium anode by about 822.3 mgh g -1 The discharge voltage of the magnesium anode was increased from 1.59 to 1.61 V, making the discharge potential stable and applicable to various current densities. The utilization efficiency of the magnesium anode was also increased to 82.2%.

[0030] Furthermore, the magnesium battery rare earth chloride electrolyte provided by the present invention is not only green and environmentally friendly, but also has a relatively low preparation cost and high economic benefits because it is prepared using non-toxic and relatively inexpensive sodium chloride, yttrium chloride and gadolinium chloride.

[0031] See also Figure 1 The present invention provides a method for preparing a rare earth chloride electrolyte for a magnesium battery, comprising the following steps: Step 1) According to the electrolyte containing 0.45-0.65M sodium chloride, 0.4-0.6M yttrium chloride, and 0.4-0.6M gadolinium chloride in a molar dispersion, the required amounts of sodium chloride, yttrium chloride, and gadolinium chloride are weighed and uniformly mixed to obtain a mixture.

[0032] Step 2) Add the mixture to deionized water and heat and stir until a transparent solution is obtained.

[0033] To prevent overheating during dissolution and to ensure that the solution temperature does not rise sharply, the mixture is added to a 1 L beaker with a spatula. A glass rod is then used to drain the mixture, and the deionized water is slowly poured along the inner wall of the beaker into the mixed material to ensure uniform dissolution of the mixture and prevent partial overdissolution. A rotor is then added to stir and the mixture is heated until the solution becomes transparent.

[0034] The stirring speed is controlled at 200-300 rpm / min.

[0035] The temperature during heating is controlled at 50±5°C.

[0036] Step 3) Add dilute hydrochloric acid or sodium hydroxide to the transparent solution to adjust the pH of the solution to 7.0±0.2, thereby obtaining a rare earth chloride electrolyte comprising, by mole fraction, 0.45-0.65 M sodium chloride, 0.4-0.6 M yttrium chloride, and 0.4-0.6 M gadolinium chloride.

[0037] When adjusting the pH of the transparent solution, a pH-conductivity meter is used for detection and adjustment.

[0038] The present invention provides a method for preparing a rare earth chloride electrolyte for a magnesium battery. The preparation method is simple, easy to prepare, and convenient and quick.

[0039] The present invention also provides a method for using a rare earth chloride electrolyte for a magnesium battery, comprising the following steps: 1) Apply an external current to the electrochemical workstation.

[0040] The current density applied by the electrochemical workstation is 2.5-10 mA cm -2 .

[0041] 2) Collect battery voltage change signals.

[0042] 3) inserting a magnesium anode and an air cathode into the electrolyte to perform electrolysis.

[0043] The magnesium anode is a Mg-0.2Ca anode, with a magnesium content of ≥99.9wt.%, a calcium content of ≥0.2wt.%, a tin content of 0.01-0.012wt.%, and a content of impurities such as manganese of ≤0.01wt.%.

[0044] Wherein, 10-15% of the surface area of ​​the magnesium anode is exposed on the surface of the electrolyte.

[0045] The air cathode is prepared by pressing and shearing a material including a copper mesh, graphite powder and foil at a pressure of 450 to 550 MPa.

[0046] The following comparative examples and examples further illustrate a rare earth chloride electrolyte for magnesium batteries, its preparation method, and its use method provided by the present invention. It is hereby noted that the following examples merely illustrate the implementation methods of the present invention. Those skilled in the art may make non-essential and appropriate improvements to the implementation methods after becoming proficient in the operation, and the implementation methods are not limited to the examples provided by the present invention.

[0047] Comparative Example 1 Deionized water was added to sodium chloride and stirred using a 45 mm rotor at a stirring speed of 120 rpm. The solution was monitored using a pH-conductivity meter until the pH value reached 7.0±0.2 to prepare a comparative electrolyte.

[0048] The method of using the electrolyte prepared in this comparative example is: Mg-0.2Ca alloy was used as the air battery anode, and the electrolyte used was 0.6M sodium chloride. A Princeton electrochemical workstation was used to apply power to the magnesium anode material. The anode composition included ≥99.9wt.% magnesium, 0.19-0.21wt.% calcium, 0.01-0.012wt.% tin, and ≤0.01wt.% impurities such as manganese and iron. The applied current density was 2.5mA cm -2 With 10mA cm -2The cathode material is prepared by 500MPa pressure treatment and shearing, and is composed of copper mesh, platinum sheet and graphite powder.

[0049] Before the experiment began, the anode sample was polished with sandpaper until the particle size was 4500. After polishing, it was sprayed with alcohol and blown dry, and cooled to room temperature. The Mg-0.2Ca anode material was placed in the electrolyte prepared in Comparative Example 1 for about 24 hours. The area exposed to the electrolyte in the impedance analysis test was about 1 cm -2 , set the test frequency to 10 -2 ~10 5 Hz, and the material impedance analysis diagram is shown in Figure 2(a).

[0050] The Mg-0.2Ca alloy anode material was placed in the electrolyte prepared in Comparative Example 1 for 3 h and 24 h, respectively. The area exposed to the electrolyte in the potentiodynamic polarization test was about 1 cm -2 The scanning rate of the potentiodynamic polarization test was 0.333 mV s -1 The cathodic scan starts at 300 mV below the open circuit potential and ends when the current density reaches 10 mA cm -2 , the potential polarization diagram of the anode material in the electrolyte is obtained as follows Figure 3 shown.

[0051] The Mg-0.2Ca anode material was placed in the electrolyte prepared in Comparative Example 1 and allowed to stand at room temperature for seven days. The size of the magnesium anode used was 10×10×3 mm. The macroscopic morphology of the anode with weight loss after seven days was as follows: Figure 4 (a) shown.

[0052] After discharge, the Mg-0.2Ca anode was drawn in the electrolyte prepared in Comparative Example 1 at a discharge current density of 2.5 mA cm -2 and 10 mA cm -2 The potential curve after discharging for 10 hours is as follows: Figure 5 shown.

[0053] At a discharge current density of 2.5 mA cm -2 and 10 mA cm -2 When the discharge test duration is 10 h, the weight loss of the Mg-0.2Ca anode material after discharge in the electrolyte prepared in Comparative Example 1 is recorded, and the anode utilization efficiency and discharge specific capacity are obtained as shown in Table 1.

[0054] As can be seen from Figure 2(a), after immersion for more than 1 hour, the magnesium anode shows a small capacitive arc at different time points in the electrolyte prepared in Comparative Example 1. After long-term immersion, an obvious inductive arc will appear. This means that the corrosion resistance of the Mg-0.2Ca anode in the electrolyte prepared in Comparative Example 1 is poor, indicating that the utilization efficiency and specific capacitance of the Mg-0.2Ca anode during the discharge test are relatively low.

[0055] The fitted impedance data of the Mg-0.2Ca anode immersed in the electrolyte prepared in Comparative Example 1 for a certain period of time are shown in Table 1.

[0056] Table 1

[0057]

[0058] From Table 1, we can see that as the immersion time increases, the polarization impedance (R p ) continued to decline and was only 258.1Ωcm at 24h. -2 , indicating that the Mg-0.2Ca anode cannot maintain high corrosion resistance in the electrolyte prepared in Comparative Example 1.

[0059] from Figure 3 As can be seen, the cathode polarization curve shifts to the right with increasing immersion time, indicating that the dissolution tendency of the Mg-0.2Ca anode in the electrolyte prepared in Comparative Example 1 increases with discharge time. Similar to the impedance results, this indicates that the anode exhibits poor corrosion resistance in the electrolyte prepared in Comparative Example 1.

[0060] The macroscopic morphology of the Mg-0.2Ca anode after being immersed in the electrolyte prepared in Comparative Example 1 for 7 days is as follows: Figure 4 As shown in (a), it can be seen that the anode has been severely corroded at this time, and the anode has dissolved from a block to an irregular shape, indicating that the electrolyte prepared in Comparative Example 1 cannot provide protection for the Mg-0.2Ca anode. When used as an electrolyte, it is not conducive to improving the anode utilization efficiency.

[0061] from Figure 5 It can be seen that the Mg-0.2Ca anode has a high -2 The discharge voltage is 1.59 V at the current density, and the voltage shows an obvious downward shift at the initial discharge stage. -2 At this time, the average discharge voltage is only 1.46 V, indicating that the voltage of the Mg-0.2Ca anode in the electrolyte prepared in Comparative Example 1 is low and the voltage fluctuation is large.

[0062] The Mg-0.2Ca anode was used in the electrolyte prepared in Comparative Example 1 at a discharge current density of 10 mA cm -2The surface morphology after 10 hours of discharge is as follows Figure 6 As shown in (a), it was observed that a large amount of discharge products were deposited on the surface of the anode. The discharge products reduced the contact area between the anode and the electrolyte and significantly reduced the discharge voltage.

[0063] The utilization efficiency and specific capacitance changes of the Mg-0.2Ca anode after discharge in the electrolyte prepared in Comparative Example 1 are shown in Table 2. As can be seen from Table 2, the utilization efficiency and specific capacitance of the anode in the electrolyte prepared in Comparative Example 1 are low, and the discharge performance is poor.

[0064] The calculation formula of anode utilization efficiency is as follows: (1) ; The specific capacitance calculation formula is as follows: (2); The theoretical weight loss calculation formula is as follows: (3).

[0065] Among them, W theo represents the theoretical anode weight loss, △W represents the actual weight loss, t represents the discharge time, I represents the current density, F represents the Faraday constant, and x ... Faraday constant. i Indicates the valence state of Mg and Ca elements, n i Indicates the mass fraction of each element in the anode, m i Indicates the relative atomic mass of each element in the anode.

[0066] Formula (1-3) shows that the anode utilization efficiency and specific capacitance depend on the actual reaction weight loss. The actual reaction weight loss of the anode can be Figure 7 This indicates that the anode reaction weight loss depends on the real-time hydrogen evolution rate during discharge. Lower hydrogen evolution rates indicate less mass loss during discharge, leading to higher utilization efficiency and specific capacitance. Conversely, higher hydrogen evolution rates indicate greater mass loss during discharge, leading to lower utilization efficiency and specific capacitance.

[0067] from Figure 7 It can be seen that the Mg-0.2Ca anode in the electrolyte prepared in Comparative Example 1 has a high -2 The real-time hydrogen evolution rate after 10 h of discharge at the current density is relatively high. The real-time hydrogen evolution rate of the Mg-0.2Ca anode in the electrolyte prepared in Comparative Example 1 is as high as 3.9 mL cm -2 This shows that the Mg-0.2Ca anode has a large mass loss during the discharge process, and its utilization efficiency and specific capacitance are low.

[0068] In summary, the discharge voltage, utilization efficiency and specific capacitance of the Mg-0.2Ca anode in the electrolyte prepared in Comparative Example 1 were not improved.

[0069] Example 1 In the rare earth chloride electrolyte for a magnesium battery provided in Example 1 of the present invention, the concentration of sodium chloride is 0.6M and the concentration of yttrium chloride is 0.5M.

[0070] The method for preparing a rare earth chloride electrolyte for a magnesium battery provided in Example 1 of the present invention comprises: Mixing sodium chloride and yttrium chloride to prepare a mixed material; Add appropriate amount of deionized water to the mixed material; The mixed materials were stirred using a 45 mm rotor at a stirring speed of 150 rpm; and heated while stirring at 45° C. The solution was monitored using a pH-conductivity meter until the pH value was 7.0±0.2, thereby obtaining the rare earth chloride electrolyte of Example 1 of the present invention. The method for using the rare earth chloride electrolyte prepared in Example 1 of the present invention is as follows: Mg-0.2Ca alloy was used as the anode of the air battery. The electrolyte used was the rare earth chloride electrolyte prepared in Example 1 of the present invention. The Mg-0.2Ca anode material was energized using a Princeton electrochemical workstation. The specific composition of the anode included ≥99.9wt.% magnesium, 0.19-0.21wt.% calcium, 0.01-0.012wt.% tin, and ≤0.01wt.% impurity elements such as manganese and iron. The applied current density was 2.5mA cm -2 With 10mA cm -2 The cathode material is prepared by 500MPa pressure treatment and shearing, and is composed of copper mesh, platinum sheet and graphite powder.

[0071] Before the experiment begins, the anode sample needs to be polished with sandpaper until the particle size is 4500. After polishing, spray it with alcohol and blow dry, then cool it to room temperature. The Mg-0.2Ca anode material is placed in the rare earth chloride electrolyte prepared in Example 1 for about 24 hours. The area exposed to the electrolyte in the impedance analysis test is about 1cm -2 , set the test frequency to 10 -2 ~10 5 Hz, and the impedance analysis diagram of the anode material is shown in Figure 2(b).

[0072] The Mg-0.2Ca alloy anode material was placed in the rare earth chloride electrolyte prepared in Example 1 for 3 h and 24 h, respectively. The area exposed to the electrolyte in the potentiodynamic polarization test was about 1 cm -2 The scanning rate of the potentiodynamic polarization test was 0.333 mV s -1The cathodic scan starts at 300 mV below the open circuit potential and ends when the current density reaches 10 mA cm -2 ; The potential polarization diagram of the anode material in the electrolyte is obtained as follows Figure 3 shown.

[0073] The Mg-0.2Ca anode material was placed in the rare earth chloride electrolyte prepared in Example 1 and allowed to stand at room temperature for seven days. The size of the Mg-0.2Ca anode used was 10×10×3 mm. The macroscopic morphology of the anode after seven days of weight loss was as follows: Figure 4 (b) shown.

[0074] After the discharge is completed, the Mg-0.2Ca anode is drawn in the rare earth chloride electrolyte prepared in Example 1 at a discharge current density of 2.5 mA cm -2 and 10 mA cm -2 The discharge potential curve after 10 h of discharge is shown in the following figure: Figure 5 shown.

[0075] At a discharge current density of 2.5 mA cm -2 and 10 mA cm -2 The discharge test duration was 10 h; the weight loss of the Mg-0.2Ca anode material after discharge in the rare earth chloride electrolyte prepared in Example 1 was recorded, and the anode utilization efficiency and discharge specific capacity were obtained as shown in Table 1.

[0076] Figure 2(b) shows that the capacitive reactance arc of the Mg-0.2Ca anode material in the rare earth chloride electrolyte prepared in Example 1 increases with the immersion time, indicating that the corrosion resistance of the anode is improved compared with that of Comparative Example 1.

[0077] Table 1 shows the fitted impedance data obtained after immersing the Mg-0.2Ca anode in the rare earth chloride electrolyte prepared in Example 1 of the present invention for a certain period of time, and the inhibition efficiency is calculated. When the immersion reaches 24 hours, the polarization resistance of the Mg-0.2Ca anode material reaches 5530Ω cm -2 , the inhibition efficiency reached 95.3%, indicating that Example 1 greatly improved the corrosion resistance of the anode, which may help to improve the anode utilization efficiency and specific capacitance.

[0078] The potentiodynamic polarization diagram of Mg-0.2Ca anode in rare earth chloride electrolyte prepared in Example 1 is shown in FIG. Figure 3 As shown in the figure, compared with the polarization curve of 3 h, the polarization curve of 24 h shifted significantly to the left, indicating that the corrosion and dissolution of the Mg-0.2Ca anode was inhibited.

[0079] Figure 4(b) is the macroscopic morphology of the Mg-0.2Ca anode after immersion in the rare earth chloride electrolyte prepared in Example 1 for 7 days. Compared with the irregular material in Comparative Example 1, Example 1 improves the corrosion resistance, but the Mg-0.2Ca anode material in Example 1 still shows obvious pitting, indicating that Example 1 has limited ability to improve the corrosion resistance of the Mg-0.2Ca anode material. When the Mg-0.2Ca anode dissolves in the discharge state, the pH at the metal / solution interface increases significantly due to the cathode hydrogen evolution, and local OH - The content increased significantly. After the introduction of yttrium chloride, Y 3+ + 3OH - → Y(OH)3, the solubility product constant of Y(OH)3 is 1.6×10 -23 , and the solubility product constant of Mg(OH)2 is 5.6×10 -12 , indicating that Y(OH)3 preferentially deposits on the surface of the Mg-0.2Ca anode. Y(OH)3 has better compactness than Mg(OH)2, effectively protecting the anode and enhancing corrosion resistance.

[0080] Figure 5 The discharge voltage curve of the Mg-0.2Ca anode after 10 h of discharge in the rare earth chloride electrolyte prepared in Example 1 is shown. It was observed that Example 1 could not effectively increase the discharge voltage.

[0081] Figure 6 (b) Mg-0.2Ca anode at 10 mA cm -2 Surface morphology after 10h discharge at the current density. Figure 6 It can be seen that after the anode is discharged in the rare earth chloride electrolyte prepared in Example 1, a large amount of discharge products are deposited on the surface. Although the amount of discharge products generated is less than that in the electrolyte prepared in Comparative Example 1, it still hinders the charge transfer and is not conducive to increasing the discharge voltage. Comparing the anode utilization efficiency and specific capacitance after discharge, it is found that the Mg-0.2Ca anode shows a utilization efficiency of 69.2% and a specific capacitance of 1463.8 mAh g in the rare earth chloride electrolyte prepared in Example 1. -1 The specific capacitance of Mg-0.2Ca anode is shown in Table 1, indicating that the formed Y(OH)3-rich discharge product layer weakens the self-corrosion process of Mg-0.2Ca anode during discharge to some extent.

[0082] The utilization efficiency and specific capacitance changes of the Mg-0.2Ca anode after discharge in the rare earth chloride electrolyte prepared in Example 1 are shown in Table 2. As can be seen from Table 2, the utilization efficiency and specific capacitance of the anode in the rare earth chloride electrolyte prepared in Example 1 are not high, and the discharge performance is average.

[0083] Figure 7This is a graph showing the real-time hydrogen evolution rate of the Mg-0.2Ca anode when discharged in the rare earth chloride electrolyte prepared in Example 1 for 10 h. The real-time hydrogen evolution rate at this time is 2.8 mL cm -2 Compared with comparative example 1, the real-time hydrogen evolution amount is reduced by about 1.1 mL cm -2 , indicating that the rare earth chloride electrolyte prepared in Example 1 can reduce the weight loss of the Mg-0.2Ca anode during the discharge process.

[0084] In summary, the electrolyte of Example 1 of the present invention contains a large amount of OH produced by the partial dissolution of yttrium chloride. - The reaction forms Y(OH)3, which is insoluble in water. Comparison of the solubility product constants reveals that Y(OH)3 is significantly lower than Mg(OH)2 and is more inclined to deposit on the surface of the Mg-0.2Ca anode. The deposition of Y(OH)3 reduces the content of loose and porous Mg(OH)2, improving the corrosion resistance of the anode. At the same time, it inhibits the real-time hydrogen evolution of the Mg-0.2Ca anode, reduces the amount of hydrogen evolved during discharge, and improves the anode utilization efficiency and specific capacitance. However, the effect of single yttrium chloride on improving discharge performance is limited. The pitting corrosion of the anode after long-term immersion and the low discharge voltage illustrate this problem.

[0085] Example 2 In the rare earth chloride electrolyte for a magnesium battery provided in Example 2 of the present invention, the concentration of sodium chloride is 0.6M and the concentration of gadolinium chloride is 0.5M.

[0086] The preparation method of a rare earth chloride electrolyte for a magnesium battery provided in Example 2 of the present invention is the same as that in Example 1.

[0087] The usage and testing methods of the rare earth chloride electrolyte for magnesium batteries prepared in Example 2 of the present invention are the same as those in Example 1.

[0088] As can be seen from Figure 2(c), after the Mg-0.2Ca anode material is immersed in the rare earth chloride electrolyte prepared in Example 2 for 1 hour, the capacitive arc increases significantly, indicating that in the short term, the rare earth chloride electrolyte prepared in Example 2 can effectively improve the corrosion resistance of the anode.

[0089] As can be seen from Table 1, the impedance fitting values ​​of the Mg-0.2Ca anode after soaking in the rare earth chloride electrolyte prepared in Example 2 for different times. When soaked for 1 hour, the polarization resistance of the Mg-0.2Ca anode material reaches 10144Ω cm -2 , the inhibition efficiency reached 87.9%. However, when the immersion time increased to 24h, the polarization resistance was only 2031.5Ω cm -2 , indicating that Example 2 has limited effect in improving the corrosion resistance of the Mg-0.2Ca anode, but may help to improve the anode utilization efficiency and specific capacitance.

[0090] from Figure 3 It can be seen that by comparing the movement of the polarization curves, it is found that the 24-hour polarization curve moves significantly to the right, indicating that the rare earth chloride electrolyte prepared in Example 2 cannot continuously inhibit the corrosion process of the Mg-0.2Ca anode.

[0091] from Figure 4 (c) It can be seen that compared with Comparative Example 1, after removing the corrosion products, the amount of Mg-0.2Ca anode remaining in the rare earth chloride electrolyte prepared in Example 2 is larger, indicating that although the rare earth chloride electrolyte prepared in Example 2 improves the corrosion resistance, the effect is not obvious. 3+ + 3OH - → Gd (OH) 3, the solubility product constant of Gd (OH) 3 is 2.0×10 -23 , and the solubility product constant of Mg(OH)2 is 5.6×10 -12 , which means that Gd(OH)3 preferentially deposits on the surface of the Mg-0.2Ca anode. Although Gd(OH)3 is more compact than Mg(OH)2, it is weaker than Y(OH)3. Therefore, the corrosion resistance of the Mg-0.2Ca anode in the rare earth chloride electrolyte prepared in Example 2 is worse than that of Comparative Example 1, but worse than that of Example 1.

[0092] from Figure 5 It can be seen that, similar to Example 1, the rare earth chloride electrolyte prepared in Example 2 cannot effectively increase the discharge voltage.

[0093] See also Figure 6 (c) at 10 mA cm -2 At this current density, after 10 h of discharge, a large amount of discharge products were deposited on the surface of the Mg-0.2Ca anode in the rare earth chloride electrolyte prepared in Example 2. These discharge products hindered the continuous contact between the anode and the electrolyte, reducing the electrochemical activity and hindering the improvement of the discharge voltage. Comparison of the anode utilization efficiency and specific capacitance after discharge revealed that the Mg-0.2Ca anode exhibited a utilization efficiency of 63% and a specific capacitance of 1422.5 mAh g in the rare earth chloride electrolyte prepared in Example 2. -1 The specific capacitance is higher than that of Comparative Example 1. The Gd(OH)3 discharge product layer generated after the introduction of gadolinium chloride inhibits the excessive dissolution of the Mg-0.2Ca anode and improves the discharge performance.

[0094] The utilization efficiency and specific capacitance changes of the Mg-0.2Ca anode after discharge in the rare earth chloride electrolyte prepared in Example 2 are shown in Table 2. As can be seen from Table 2, the utilization efficiency and specific capacitance of the anode in the rare earth chloride electrolyte prepared in Example 2 are not high, and the discharge performance is average.

[0095] See also Figure 7When the Mg-0.2Ca anode was discharged in the rare earth chloride electrolyte prepared in Example 2 for 10 h, its real-time hydrogen evolution capacity was 2.9 mL cm -2 Compared with comparative example 1, the real-time hydrogen evolution amount is reduced by about 1 mL cm -2 , indicating that the rare earth chloride electrolyte prepared in Example 2 can reduce the mass loss of the Mg-0.2Ca anode during the discharge process.

[0096] In summary, gadolinium chloride also dissolves into OH produced at the anode / electrolyte interface. - The reaction forms Gd(OH)3, which is insoluble in water. Due to its low solubility product constant, it is more easily deposited on the surface of the Mg-0.2Ca anode, inhibiting the deposition of Mg(OH)2 in the porous pores under corrosion and discharge conditions, thereby improving the anode utilization efficiency and specific capacitance. However, similar to the electrolyte formed by a single yttrium chloride, the effect of single gadolinium chloride on improving the discharge performance of the Mg-0.2Ca anode is limited.

[0097] Example 3 In a rare earth chloride electrolyte for a magnesium battery provided in Example 3 of the present invention, the concentration of sodium chloride is 0.6M, the concentration of yttrium chloride is 0.5M, and the concentration of gadolinium chloride is 0.5M.

[0098] The preparation method of a rare earth chloride electrolyte for a magnesium battery provided in Example 3 of the present invention is the same as that in Example 1.

[0099] The usage and testing methods of the rare earth chloride electrolyte for magnesium batteries prepared in Example 3 of the present invention are the same as those in Example 1.

[0100] As can be seen from Figure 2(d), the capacitive reactance arc of the Mg-0.2Ca anode in the rare earth chloride electrolyte prepared in Example 3 is the largest after immersion for 24 hours, which proves that the corrosion resistance of the anode material in the rare earth chloride electrolyte prepared in Example 3 is the best.

[0101] Table 1 shows the fitted impedance data obtained after the Mg-0.2Ca anode was immersed in the rare earth chloride electrolyte prepared in Example 3 of the present invention for a certain period of time. As shown in Table 1, when the immersion time reaches 24 hours, the polarization impedance value of the Mg-0.2Ca anode is 8891Ω cm -2 , the inhibition efficiency is as high as 97.1%.

[0102] See also Figure 3 After the Mg-0.2Ca anode was immersed in the rare earth chloride electrolyte prepared in Example 3 for 24 h, the cathode polarization curve shifted significantly to the right, which also shows that the rare earth chloride electrolyte prepared in Example 3 of the present invention is most helpful in inhibiting the self-corrosion phenomenon of the Mg-0.2Ca anode.

[0103] See also Figure 4 (d) It can be seen that the surface of the Mg-0.2Ca anode is flat after being immersed in the rare earth chloride electrolyte prepared in Example 3 for seven days, and the material still maintains a block shape, indicating that the rare earth chloride electrolyte prepared in Example 3 has a long-term protective effect on the anode material.

[0104] See also Figure 5 It can be seen that the Mg-0.2Ca anode material has a high conductivity at 2.5 mA cm in the rare earth chloride electrolyte prepared in Example 3. -2 At the current density of 10 mA cm, the average discharge voltage reached 1.6 V, and the discharge voltage curve was stable, indicating that the rare earth chloride electrolyte prepared in Example 3 can greatly improve the discharge performance of the anode. -2 Under different current densities, the rare earth chloride electrolyte prepared in Example 3 can still significantly increase the discharge voltage by about 400 mV, which indicates that the discharge performance of the Mg-0.2Ca anode in the rare earth chloride electrolyte prepared in Example 3 is stable and reliable under different current densities.

[0105] See also Figure 6 (d) After the Mg-0.2Ca anode was discharged in the rare earth chloride electrolyte prepared in Example 3 for 10 hours, no large amount of discharge products were deposited on the surface of the Mg-0.2Ca anode, indicating that the rare earth chloride electrolyte prepared in Example 3 can effectively inhibit the deposition of discharge products on the anode surface, forming a thin and dense discharge product layer on the surface to ensure the charge transfer rate and improve the discharge voltage. Comparing the changes in utilization efficiency and specific capacity, the Mg-0.2Ca anode was discharged in the rare earth chloride electrolyte prepared in Example 3 at 10 mA cm -2 The anode utilization efficiency and specific capacity were 82.2% and 1856 mA hg, respectively. -1 The rare earth chloride electrolyte prepared in Example 3 significantly improved the discharge performance of the Mg-0.2Ca anode and has great potential for industrial application.

[0106] The utilization efficiency and specific capacitance changes of the Mg-0.2Ca anode after discharge in the rare earth chloride electrolyte prepared in Example 3 are shown in Table 2. As can be seen from Table 2, the utilization efficiency and specific capacitance of the anode in the rare earth chloride electrolyte prepared in Example 3 are high, and the discharge performance is good.

[0107] See also Figure 7 By comparing the real-time hydrogen evolution rate, it can be seen that the real-time hydrogen evolution rate of the Mg-0.2Ca anode in the rare earth chloride electrolyte prepared in Example 3 is only 2.5 mL cm -2 , which shows that the rare earth chloride electrolyte prepared in Example 3 can effectively inhibit the self-corrosion process of the anode during discharge, reduce the mass loss of the anode and improve the utilization efficiency and specific capacitance.

[0108] This is because yttrium chloride and gadolinium chloride are introduced at the same time. 3+ 、Gd 3+ With OH - The reaction tendency is significantly higher than that of Mg 2 + , a protective layer rich in Gd(OH)3 and Y(OH)3 is deposited on the surface of Mg-0.2Ca anode. -23 ) has a solubility product constant slightly higher than that of Y(OH)3 (1.6×10 -23 ), the preferentially deposited Y(OH)3 will provide more nucleation sites for the formation of Gd(OH)3, further promoting the deposition of Gd(OH)3 and densifying the surface film layer of Mg-0.2Ca anode.

[0109] In summary, the Mg-0.2Ca anode is in the rare earth chloride electrolyte prepared in Example 3 of the present invention, under discharge conditions, due to the Gd 3+ 、Y 3+ The combined effects of the two, form a thin layer rich in Gd(OH)3 and Y(OH)3 on the surface. This thin layer not only ensures ion transport but also inhibits the self-corrosion process of the anode material, resulting in the Mg-0.2Ca anode exhibiting extremely high electrochemical performance in the rare earth chloride electrolyte prepared in Example 3.

[0110] Table 2

[0111] Example 4 In a rare earth chloride electrolyte for a magnesium battery provided in Example 4 of the present invention, the concentration of sodium chloride is 0.45M, the concentration of yttrium chloride is 0.4M, and the concentration of gadolinium chloride is 0.4M. The preparation method of a rare earth chloride electrolyte for a magnesium battery provided in Example 4 of the present invention is the same as that in Example 1; The method for using the rare earth chloride electrolyte for magnesium batteries prepared in Example 4 of the present invention is the same as that in Example 1.

[0112] The utilization efficiency and specific capacitance changes of the Mg-0.2Ca anode after discharge in the rare earth chloride electrolyte prepared in Example 4 of the present invention are shown in Table 2. As can be seen from Table 2, the utilization efficiency and specific capacitance of the anode in the rare earth chloride electrolyte prepared in Example 4 are high, and the discharge performance is good.

[0113] Example 5 In a rare earth chloride electrolyte for a magnesium battery provided in Example 5 of the present invention, the concentration of sodium chloride is 0.55M, the concentration of yttrium chloride is 0.45M, and the concentration of gadolinium chloride is 0.5M. The preparation method of a rare earth chloride electrolyte for a magnesium battery provided in Example 5 of the present invention is the same as that in Example 1; The method of using the rare earth chloride electrolyte for magnesium batteries prepared in Example 5 of the present invention is the same as that in Example 1.

[0114] The utilization efficiency and specific capacitance changes of the Mg-0.2Ca anode after discharge in the rare earth chloride electrolyte prepared in Example 5 of the present invention are shown in Table 2. As can be seen from Table 2, the utilization efficiency and specific capacitance of the anode in the rare earth chloride electrolyte prepared in Example 5 are high, and the discharge performance is good.

[0115] Example 6 In a rare earth chloride electrolyte for a magnesium battery provided in Example 6 of the present invention, the concentration of sodium chloride is 0.65 M, the concentration of yttrium chloride is 0.6 M, and the concentration of gadolinium chloride is 0.6 M; The preparation method of a rare earth chloride electrolyte for a magnesium battery provided in Example 6 of the present invention is the same as that in Example 1; The method for using the rare earth chloride electrolyte for a magnesium battery provided in Example 6 of the present invention is the same as that in Example 1.

[0116] The utilization efficiency and specific capacitance changes of the Mg-0.2Ca anode after discharge in the rare earth chloride electrolyte prepared in Example 6 of the present invention are shown in Table 2. As can be seen from Table 2, the utilization efficiency and specific capacitance of the anode in the rare earth chloride electrolyte prepared in Example 6 are high, and the discharge performance is good.

[0117] Example 7 In a rare earth chloride electrolyte for a magnesium battery provided by Example 7 of the present invention, the concentration of sodium chloride is 0.6 M, the concentration of yttrium chloride is 0.5 M, and the concentration of gadolinium chloride is 0.4 M; The preparation method of a rare earth chloride electrolyte for a magnesium battery provided in Example 7 of the present invention is the same as that in Example 1; The method for using the rare earth chloride electrolyte for a magnesium battery provided in Example 7 of the present invention is the same as that in Example 1.

[0118] The utilization efficiency and specific capacitance changes of the Mg-0.2Ca anode after discharge in the rare earth chloride electrolyte prepared in Example 7 of the present invention are shown in Table 2. As can be seen from Table 2, the utilization efficiency and specific capacitance of the anode in the rare earth chloride electrolyte prepared in Example 7 are high, and the discharge performance is good.

[0119] Example 8 In a rare earth chloride electrolyte for a magnesium battery provided by Example 8 of the present invention, the concentration of sodium chloride is 0.5 M, the concentration of yttrium chloride is 0.55 M, and the concentration of gadolinium chloride is 0.5 M; The preparation method of a rare earth chloride electrolyte for a magnesium battery provided in Example 8 of the present invention is the same as that in Example 1; The method for using the rare earth chloride electrolyte for a magnesium battery provided in Example 8 of the present invention is the same as that in Example 1.

[0120] The utilization efficiency and specific capacitance changes of the Mg-0.2Ca anode after discharge in the rare earth chloride electrolyte prepared in Example 8 of the present invention are shown in Table 2. As can be seen from Table 2, the utilization efficiency and specific capacitance of the anode in the rare earth chloride electrolyte prepared in Example 8 are high, and the discharge performance is good.

[0121] Example 9 In a rare earth chloride electrolyte for a magnesium battery provided in Example 9 of the present invention, the concentration of sodium chloride is 0.6 M, the concentration of yttrium chloride is 0.6 M, and the concentration of gadolinium chloride is 0.6 M. The preparation method of a rare earth chloride electrolyte for a magnesium battery provided in Example 9 of the present invention is the same as that in Example 1; The method for using the rare earth chloride electrolyte for a magnesium battery provided in Example 9 of the present invention is the same as that in Example 1.

[0122] The utilization efficiency and specific capacitance changes of the Mg-0.2Ca anode after discharge in the rare earth chloride electrolyte prepared in Example 9 of the present invention are shown in Table 2. As can be seen from Table 2, the utilization efficiency and specific capacitance of the anode in the rare earth chloride electrolyte prepared in Example 9 are high, and the discharge performance is good.

[0123] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solutions of the present invention and are not limiting. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A rare earth chloride electrolyte for a magnesium battery, characterized in that: In terms of mole fraction, its components include 0.45-0.65M sodium chloride, 0.4-0.6M yttrium chloride, and 0.4-0.6M gadolinium chloride; The pH of the electrolyte is 7±0.

2.

2. A method for preparing a rare earth chloride electrolyte for a magnesium battery according to claim 1, characterized in that: The steps include: Taking required amounts of sodium chloride, yttrium chloride and gadolinium chloride and mixing them evenly to obtain a mixture; Add the mixture into deionized water and heat and stir until a transparent solution is obtained; Dilute hydrochloric acid or sodium hydroxide is added to the transparent solution to adjust the pH of the solution to 7.0±0.2 to obtain the electrolyte.

3. The method for preparing a rare earth chloride electrolyte for a magnesium battery according to claim 2, wherein: The stirring speed is controlled at 200-300 rpm / min.

4. The method for preparing a rare earth chloride electrolyte for a magnesium battery according to claim 2, wherein: The heating temperature is 50±5°C.

5. The method for preparing a rare earth chloride electrolyte for a magnesium battery according to claim 2, wherein: The pH value of the transparent solution is detected by a pH-conductivity meter.

6. A method for using the rare earth chloride electrolyte for magnesium batteries according to claim 1, characterized in that: The steps include: Apply an external current to the electrochemical workstation; Collect battery voltage change signals; A magnesium anode and an air cathode are inserted into the electrolyte to perform electrolysis.

7. The method for using the rare earth chloride electrolyte for magnesium batteries according to claim 6, characterized in that: The current density applied by the electrochemical workstation is 2.5-10 mA·cm -2 .

8. The method for using the rare earth chloride electrolyte for magnesium batteries according to claim 6, characterized in that: The magnesium anode is a Mg-0.2Ca anode, with a magnesium content of ≥99.9 wt.%, a calcium content of ≥0.2 wt.%, a tin content of 0.01-0.012 wt.%, and a content of impurities such as manganese of ≤0.01 wt.%.

9. The method for using the rare earth chloride electrolyte for magnesium batteries according to claim 6, characterized in that: In the electrolyte, 10-15% of the surface area of ​​the magnesium anode is exposed on the surface of the electrolyte.

10. The method for using the rare earth chloride electrolyte for magnesium batteries according to claim 6, characterized in that: The air cathode is prepared by using materials including copper mesh, graphite powder and foil through 450-550 MPa pressure pressing and shearing treatment.

Citation Information

Patent Citations

  • Choline ionic liquid, synthesis method and application thereof as electrolyte additive for magnesium-air battery

    CN116239463B

  • Electrolyte containing sodium dihydrogen phosphate additive and application of electrolyte in magnesium air battery

    CN118610664A

  • Magnesium-aluminum-indium rare earth anode material and preparation method thereof, and magnesium air cell

    CN109136598A

  • Composite corrosion inhibitor electrolyte, application thereof and magnesium air battery

    CN110364787A

  • Magnesium ion battery negative electrode material, magnesium ion battery and preparation method thereof

    CN111244451A